Reference values and reliability for lumbopelvic strength and endurance in asymptomatic subjects - Oliveira, Isadora O. de; Pilz, Bruna; Santos, Roberto L.G.; Vasconcelos, Rodrigo A.; Mello, Wilson; Grossi, Débora B. (Revista brasileira de fisioterapia (São Carlos (São Paulo, Brazil)), 2018)
•The set of tests presented good reliability for the lumbopelvic region.•Reference values may contribute for clinical practice assessments.•SEM, TEM and MDC values confirm the set of tests’ usage in clinical practice. Assessing the lumbopelvic region is useful for detecting many musculoskeletal dysfunctions and also performance deficits. Several clinical tests are used to assess this region, however, reference values and results related to method, reliability and error measurements of these tests have not been reported. To establish reference values and determine reliability, standard error of measurement (SEM), typical error of measurement (TEM) and minimum detectable change (MDC) of a set of clinical tests used for assessing the lumbopelvic region in subjects divided by gender, age group and physical activity levels. An observational study was conducted. For reference values, 152 subjects performed eight clinical tests (isometric strength of hip muscles; deep abdominal function and endurance tests) used to assess the lumbopelvic region. Reliability analyses were assessed using the Intraclass Correlation Coefficient (ICC2,1) and error measurements were calculated by using the SEM, TEM and the MDC. Reference values were established for each group and results showed significant (p<0.05) differences concerning gender, age group and physical activity levels in clinical tests. All tests presented good reliability indices with an ICC higher than 0.80 for reliability; MDC values were greater than mean of SEM in all tests, confirming its usage for clinical practice assessments. Reference values are necessary in the evaluation of subjects and these results can contribute for clinical practice, providing clinical training targets. Also, evaluation of reliability and error measurements in this set of tests allows its use in clinical practice.